Identification of Trichophyton sp. Fungus in the Toe-Crosses of Leather Cracker Workers in Indramayu District - Ibrahim Aji, Rizal; Tri Ananda, Keysha; Supenah, Pipin; Ubaedillah, Muhammad Ibnu (Universitas An Nasher - Cirebon, 2025)
Dermatophytosis is a skin infection caused by dermatophyte fungi, one of which is Trichophyton sp, which can grow in humid conditions such as between the toes. Indramayu District is an area with many skin cracker industry workers who are susceptible to exposure to humid work environments. This study aims to determine which skin cracker workers are infected with Trichophyton sp fungi, and to determine the percentage of skin cracker workers infected with Trichophyton sp fungi. Initial observations were made on 44 workers, and 30 people showed symptoms such as itching, scaly or peeling skin, and redness so that they met the criteria to be used as samples. The study was conducted using a descriptive survey method using a questionnaire and macroscopic and microscopic laboratory examination of skin scrapings from between the toes. Samples were planted on Sabouraud Dextrose Agar (SDA) media and incubated for 5–7 days. The results showed that out of 30 samples, 4 samples with a percentage of 13,3% were positive for Trichophyton sp. fungus infection, while 26 samples with a percentage of 87% showed negative results. These findings indicate that humid work environments contribute to the risk of fungal infections, but other factors such as foot hygiene and immunity also play a role in preventing infection. This study is expected to be a reference for prevention efforts and improving foot hygiene for workers in humid environments.